Hipertensi Pulmonal Persisten Segera Setelah Balloon Mitral Valvuloplasty - Irwan H Siahaan; Manoefris Kasim; Amiliana M Soesanto; Ganesja M Harimurti (Jurnal Kardiologi Indonesia, 2008)
Background.Pulmonary hypertension frequently complicates mitral stenosis. Increased pulmonary artery pressure results from raised left atrial pressure, pulmonary arteriolar vasoconstriction, and obliterative changes in the pulmonary vascular bed, and usually responds to relief of mitral stenosis. However, severe pulmonary hypertension may persist after mechanical relief of mitral stenosis.Methods.A case cross sectional study was conducted in mitral stenosis patients to study the immediate effect of BMV for severe pulmonary hypertension. Pulmonary hypertension was assessed by echocardiography before procedur and 24 – 72 hours after procedure. Analysis was done to assess the relation of age, gender, left atrial size, gradient across mitral valve, mitral valve area and systolic PA pressure before procedure on the persistency of severe pulmonary hypertension.Results.There were 183 patients with mitral stenosis were found in January 2007 – December 2008. Seventy three were severe pulmonary hypertension (systolic PAP = 80 mmHg) and 61 patients were mild – moderate pulmonary hypertension ( systolic PAP < 80 mmHg). Only 54 patients were fulfilling study criteria. Of 54 cases included to analysis, 66.7% were female, 70.4% were in sinus rhytm and had age of 35.44 ± 10.55 yo. The mean mitral valve gradient (MVG) decreased from 18.53 ± 6.40 to 8.50 ± 4.84 mm Hg (p< 0.001). Mitral valve area (MVA) increased from 0.76 ± 0.26 to 1.36 ± 0.36 cm 2 (p < 0.02). LA diameter decreased from 52.87 ± 7.14 to 49.13 ± 7.35 mm (p = 0.01). The pulmonary artery systolic pressure decreased from 100.48 ± 15.77 to 79.83 ± 17.49 mm Hg (p< 0.001). Systolic PAP > 95 mmHg was associated with persistency of PH in mitral stenosis patients with 58% sensitivity and 30% specificity.Conclusions.The degree of Systolic PAP before BMV is associated with persistency of severe pulmonary hypertension. Systolic PAP > 95 mmHg was associated with persistency of PH in mitral stenosis patients with 58% sensitivity and 70% specificity.